Madrasah Social Climate and Family Support in MA Students' Motivation and Learning Achievement - Didit Darmawan; Munif Mawardi (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study aims to analyze the concept of school social climate and family support in shaping learning motivation and achievement of Madrasah Aliyah students. Employing a qualitative literature review method with content analysis, this research synthesizes academic literature to develop a conceptual understanding of how both factors influence student motivation and achievement. The findings reveal that school social climate contributes through positive teacher-student relationships, supportive peer interactions, perceptions of fairness, positive academic atmosphere, facility availability, student involvement in decision-making, physical and psychological safety, religious culture, principal leadership, parent involvement, extracurricular activities, and consistency between values and practice. Family support contributes through emotional support, appreciation, instrumental support, informational support, school involvement, realistic expectations, authoritative parenting, open communication, conducive home environment, family routines, support for interests and talents, spiritual value inculcation, involvement in future planning, and consistency with madrasah values. Optimal motivation and achievement are achieved when positive school social climate and strong family support exist simultaneously and reinforce each other. The study implies that efforts to enhance student motivation and achievement must address both school climate and family support in an integrated manner through strong school-family partnerships.